Multi-domain computerized cognitive training for children with intellectual developmental disorder: A randomized controlled trial - Wu, Jingsong; Peng, Juan; Li, Zhaoying; Deng, Haiyin; Huang, Zhenming; He, Youze; Tu, Jingnan; Cao, Lei; Huang, Jia (Frontiers in Psychology, 2023)
Purpose: To observe the effectiveness of multi-domain computerized cognitive training on intellectual and adaptive function in children with Intellectual development disorders (IDD). Methods: Sixty children with IDD participated in a 5-week randomized controlled trial, who were randomized into multi-domain computerized cognitive training (CCT) group (n=30) and traditional cognitive training (control group) group (n=30). The Chinese Wechsler Young Children scale(C-WYCSI) and the Chinese Vineland Adaptive Behavior Rating Scale (VABS-C) were used at baseline, post-training, and three-month follow-up. Results: We observed that for function, CCT caused significant improvement in the total score（FSIQ） of Wechsler Intelligence Scale（t（60）=31.97，p<0.01) and its subdomain VIQ score (t（60）=33.83，p<0.01. For adaptive function, CCT had a better ADQ score（t（60）=28.05, p<0.01), and its subdomain communication（t（60）=10.86, p<0.01） and socialization （t（60）=4.35, p<0.015). Moreover, there is a positive correlation between FSIQ changes and ADQ changes in the CCT group (rs=0.654, p<0.01). Following CCT, greater increase VIQ score was associated with a greater increase in adaptive function (bootstrapping CI: [0.16, 3.30]). Conclusion: These findings support that multi-domain computerized cognitive training would improve the intellectual and adaptive function of children with IDD.